CD10, BCL6, and MUM1 expression in diffuse large B‐cell lymphoma on FNA samples. Issue 2 (28th September 2015) - Cozzolino, Immacolata; Varone, Valeria; Picardi, Marco; Baldi, Carlo; Memoli, Domenico; Ciancia, Giuseppe; Selleri, Carmine; De Rosa, Gaetano; Vetrani, Antonio; Zeppa, Pio
Abstract : BACKGROUND: Gene expression profiling has divided diffuse large B‐cell lymphoma (DLBCL) into 2 main subgroups: germinal center B (GCB) and non‐GCB type. This classification is reproducible by immunohistochemistry using specific antibodies such as CD10, B‐cell lymphoma 6 (BCL6), and multiple myeloma oncogene 1 (MUM1). Fine‐needle aspiration (FNA) plays an important role in the diagnosis of non‐Hodgkin lymphoma, and in some cases FNA may be the only available pathological specimen. The objectives of the current study were to evaluate CD10, BCL6, and MUM1 immunostaining on FNA samples by testing the CD10, BCL6, and MUM1 algorithm on both FNA cell blocks (CB) and conventional smears (CS), evaluating differences in CB and CS immunocytochemical (ICC) performance, and comparing results with histological data. METHODS: Thirty‐eight consecutive DLBCL cases diagnosed by FNA were studied. Additional passes were used to prepare CB in 22 cases and CS in 16 cases; the corresponding sections and smears were immunostained using CD10, BCL6, and MUM1 in all cases. The data obtained were compared with histological immunostaining in 24 cases. RESULTS: ICC was successful in 33 cases (18 CB and 15 CS) and not evaluable in 5 cases (4 CB and 1 CS). The CD10‐BCL6‐MUM1 algorithm subclassified DLBCL as GCB (9 cases) and non‐GCB (24 cases). ICC data were confirmed on histologic staining in 24 cases. CONCLUSIONS: CD10, BCL6, and MUM1 ICC staining can be performed on FNA samples. The results herein prove it is reliable both on CB and CS, and is equally effective and comparable to immunohistochemistry data. Cancer (Cancer Cytopathol) 2016;124:135–143. © 2015 American Cancer Society . Abstract : The CD10‐B‐cell lymphoma 6 (BCL6)‐multiple myeloma oncogene 1 (MUM1) immunocytochemical algorithm is reliable on cell blocks and conventional smears of fine‐needle aspiration samples. The fine‐needle aspiration subclassification of diffuse large B‐cell lymphoma may provide additional prognostic information that might be useful when histological sample are not available.